(untitled) (Revista Iberoamericana de Estudios Municipales, 2018)
This mixed-method research is based on the general proposition that the greater the number of subnational jurisdictions relative to the population and the greater the number of vertical tiers of government, the greater the incentives for corruption. The specific focus is on the atomization of subnational governments and the creation of community councils as two factors of flawed political decentralization that are linked to increased corruption in Venezuela. The propositions are tested using fieldwork analysis on three subnational units of governance in Venezuela and multivariate statistical tests against a wide range of controls on 100 randomly selected countries.